Hubungan Asi Eksklusif Dengan Kejadian Diare Di Puskesmas Sidorejo Kota Pagar Alam Tahun 2022 - Herlika, Mika; Murwati, Murwati; Surahman, Fery (Gayaku Publisher, 2023)
Diarrhoea is an endemic disease, especially in developing countries such as Indonesia, and a disease that has the potential to experience extraordinary events (KLB), which are often accompanied by death. Globally, there is an increase in diarrhoea cases that cause death in children under five. WHO data (2017) states that there are around 1.7 billion cases of diarrhoea in toddlers, which causes the deaths of 525,000 toddlers each year. In 2021, the highest number of diarrhoea cases will still be in the same puskesmas, namely, Sidorejo Health Centre, with 51 cases. Gunung Dempo Health Centre with 45 cases and Pengandonan Health Centre with 37 cases The purpose of this study was to determine the relationship between exclusive breastfeeding and the incidence of diarrhoea in the Sidorejo Health Centre area in 2022. This study used quantitative methods with a cross-sectional research design. The population in this study was all mothers who had toddlers and lived in the Sidorejo Health Centre working area, namely 168 toddlers. Sampling in this study was done using the simple random sampling technique. The sample in this study was 63 people. Data collection tools used in this study were a checklist data collection format () and a research questionnaire. Data analysis used chi-square statistical analysis with a 95% confidence level and a value (p) of 0.05. Suggestions are expected for health agencies (Puskesmas) to be able to improve the improvement of clean water facilities and healthy latrine facilities and strive to increase residential environmental health programmes with the target of plastering the floor of the house. The results of this study indicate that there is a significant relationship between exclusive breastfeeding and the incidence of diarrhoea in toddlers in the Sidorejo Health Centre area of Pagar Alam City, with a value of p = 0.002.